Challenging the Vestibular System Affects Gait Speed and Cognitive Workload in Chronic Mild Traumatic Brain Injury and Healthy Adults - D'Silva, Linda; Chalise, Prabhakar; Rippee, Michael; Devos, Hannes (Frontiers in Neurology, 2022)
People with persistent symptoms after mild traumatic brain injury (mTBI) report imbalance during walking with head movements. The purpose of this study was 1) to compare usual walk gait speed to walking with head turns (HT) between people with mTBI and controls, 2) to compare the cognitive workload from usual walk to HT walk between groups, and 3) to examine if gaze stability deficits and mTBI symptoms influence gait speed. Twenty-three individuals (mean age 55.7 ± 9.3 years) with persistent symptoms after mTBI (between 3 months to 2 years post-injury) were compared with 23 age and sex-matched controls. Participants walked a 12-inch wide, 60-foot walkway when looking ahead and when walking with HT to identify letters and their colors. Gait speed during usual walk and HT walk were calculated. Pupillary responses during both walks were converted to the Index of Cognitive Activity (ICA) as a measure of cognitive workload. Gaze stability was examined by the dynamic visual acuity (DVA) test in the yaw plane. The Post-Concussion Symptom Scale (PCSS) was used to collect symptom severity. Within group analysis showed that gait speed was lower during HT walk compared to usual walk in the people with mTBI (p<0.001) as well as in controls (p<0.001). Average ICA was higher with HT compared to usual walk in the mTBI group in the right eye (p=0.01) and left eye (p=0.001), and in controls in the right eye (p=0.01) and left eye (p=0.01). Participants in the mTBI group had slower usual (p<0.001), and HT gait speed (p<0.001) compared to controls. No differences were noted in average ICA in the right or left eye during usual walk and HT walk between groups (p>0.05). DVA loss in the yaw plane to the right and left was not different between groups (p>0.05) were not correlated with gait speed. PCSS scores were correlated with usual walk (r=-0.50, p<0.001) and HT gait speed (r=-0.44, p=0.002). Slower gait speed, poorer stability, and higher cognitive workload during walking with head turns may reduce community participation in people with mTBI and persistent symptoms.